2007
DOI: 10.1080/02796015.2007.12087951
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dimensions of Social-Emotional Classroom Behavior and School Readiness for Low-Income Urban Preschool Children

Abstract: The present study identified higher-order relationships among teacher assessments of approaches to learning and emotional and behavioral adjustment constructs for urban, low-income preschool children. It examined the unique contribution of these dimensions to cognitive and social competencies and risk of poor academic outcomes. Analyses of a large, representative sample of urban Head Start children revealed two distinct and reliable, higher-order dimensions of classroom adjustment behavior: Regulated and Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(66 citation statements)
references
References 46 publications
2
56
0
8
Order By: Relevance
“…Reading engagement consists of three dimensions: behavioural (i.e., sustained attention), emotional (i.e., interest and enthusiasm) and verbal (i.e., comments on the book or reading experience; Unrau & Quirk, 2014). Observations are typically used to measure reading engagement (Fantuzzo, Bulotsky‐Shearer, McDermott, & McWayne, 2007; Mahoney & Wheeden, 1999), and the three dimensions of engagement are typically operationalized as follows: (a) visual attention as a proxy for behavioural engagement, (b) emotional expressions as a proxy for emotional engagement and (c) verbal comments as a proxy for verbal engagement.…”
Section: Screen Media Interactivity and Readingmentioning
confidence: 99%
“…Reading engagement consists of three dimensions: behavioural (i.e., sustained attention), emotional (i.e., interest and enthusiasm) and verbal (i.e., comments on the book or reading experience; Unrau & Quirk, 2014). Observations are typically used to measure reading engagement (Fantuzzo, Bulotsky‐Shearer, McDermott, & McWayne, 2007; Mahoney & Wheeden, 1999), and the three dimensions of engagement are typically operationalized as follows: (a) visual attention as a proxy for behavioural engagement, (b) emotional expressions as a proxy for emotional engagement and (c) verbal comments as a proxy for verbal engagement.…”
Section: Screen Media Interactivity and Readingmentioning
confidence: 99%
“…The importance of these behaviors has been shown in the research carried out with children from the general population. Several studies demonstrate the link between learning behaviors and academic readiness ( Fantuzzo et al, 2007 ; Vitiello et al, 2011 ), success in reading ( Jenkins and Demaray, 2015 ), and the prediction of eventual good classroom adjustment, school attendance, and future socio-behavioral adjustment ( Sasser et al, 2015 ; McDermott et al, 2016 ), or as a protective factor mitigating the negative effect of lower levels of classroom quality on dictation/spelling ( Meng, 2015 ). In fact, these learning behaviors have also been found to predict achievement beyond intelligence ( Yen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…It could be assumed that aspects of metacognition such as pro-social, cognitive, emotional and motivational can all be improved as a result of effective teaching and learning practices. It could be also concluded that young children not only are able to regulate their own engagement in learning (Perry, 1998), but it is also possible to foster these skills during the early years, with positive benefits for their academic self-belief and achievement (Fantuzzo et al, 2007), since metacognition is a key element and driver of self-regulation (Duckworth, Akerman, MacGregor, Salter, & Vorhaus, 2009). The acquisition of these skills can have long-lasting beneficial effects.…”
Section: Discussionmentioning
confidence: 99%